Montessori-based sensorial materials for children with visual impairments - Casauay, Arabelle Krystal A.
"Educational goals for children with visual impairments (CVI) in the preschool level are the same as those for regular students, involving formal subjects such as English, Mathematics, Science, etc. to prepare them for Grade 1. However, preparation of CVI to more advanced skills appear more complicated and gradual because of their limited, if not, absence of the sense of sight. Thus, different educational methods and techniques are being applied and are continuously being developed to fit the needs of the CVL